Endocrine-disrupting effects of environmental BPS and PFOS on human brain organoid development - Di Credico, Andrea; Gaggi, Giulia; Bibbò, Sandra; Blenkinsop, Timothy A.; Di Baldassarre, Angela; Ghinassi, Barbara (Frontiers in Endocrinology, 2025)
ObjectivePrenatal exposure to environmental endocrine-disrupting chemicals (EDCs) has been increasingly linked to neurodevelopmental impairment. Bisphenol S (BPS) and perfluoro-octane sulfonate (PFOS), two widely distributed EDCs detected in maternal and fetal tissues, raise concern due to their potential to interfere with brain development even at low environmental doses.Methodsa phenotypic screening on human iPSC-derived cerebral organoids was performed to explore whether chronic exposure to BPS and PFOS could affect key neurodevelopmental processes.ResultsBoth compounds affected key neurodevelopmental processes, including neuronal proliferation, cortical specification, synaptogenesis, glutamatergic differentiation, mitochondrial function, and choroid plexus formation. Importantly, TUNEL assay confirmed the absence of significant cytotoxicity. BPS exposure was associated with reduced ERβ, GPER, and phosphorylated Akt expression, suggesting a possible involvement of estrogen-related pathways. PFOS exposure coincided with decreased transthyretin expression, suggesting a potential influence on thyroid hormone availability.ConclusionsExposure to multiple EDCs may disrupt distinct endocrine axes, producing cumulative impacts on human brain development. These findings underscore the value of human-relevant models for identifying endocrine-mediated neurodevelopmental hazards. While the observed molecular changes suggest distinct hormonal pathways may be involved, future mechanistic studies, including co-exposures with receptor modulators, will be required to establish causal relationships.